2014
DOI: 10.1038/srep06402
|View full text |Cite
|
Sign up to set email alerts
|

The Effort-reward Imbalance work-stress model and daytime salivary cortisol and dehydroepiandrosterone (DHEA) among Japanese women

Abstract: We examined the influence of work-related effort–reward imbalance and overcommitment to work (OC), as derived from Siegrist's Effort–Reward Imbalance (ERI) model, on the hypothalamic–pituitary–adrenocortical (HPA) axis. We hypothesized that, among healthy workers, both cortisol and dehydroepiandrosterone (DHEA) secretion would be increased by effort–reward imbalance and OC and, as a result, cortisol-to-DHEA ratio (C/D ratio) would not differ by effort–reward imbalance or OC. The subjects were 115 healthy femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 43 publications
(76 reference statements)
0
26
0
3
Order By: Relevance
“…Other studies have found contrary results reporting no significant associations between ERI and lowered awakening cortisol (Hanson et al 2000; Harris et al 2007; Marchand et al 2016; Ota et al 2014). Steptoe et al (2004) did not find a significant association of dysregulated CAR with ERI.…”
Section: Discussionmentioning
confidence: 75%
“…Other studies have found contrary results reporting no significant associations between ERI and lowered awakening cortisol (Hanson et al 2000; Harris et al 2007; Marchand et al 2016; Ota et al 2014). Steptoe et al (2004) did not find a significant association of dysregulated CAR with ERI.…”
Section: Discussionmentioning
confidence: 75%
“…We cross-sectionally analysed the baseline dataset of a prospective cohort study which was conducted to clarify the relationship between work-related psychosocial factors and musculoskeletal disorders in nursery school teachers 41 . Table 1 presents general characteristics (age, employment status, current smoking, menstruation irregularity, ovulatory phase and health disorders), job strain and social support scores and logarithmic (log)-transformed area under the curve with respect to ground (AUC G ) 42 of salivary DHEA, cortisol and C/D ratio of the subjects.…”
Section: Resultsmentioning
confidence: 99%
“…This is concordant with the existing evidence 38 40 . We reported that effort–reward imbalance and overcommitment to work, as derived from the Effort–Reward Imbalance (ERI) model 47 , were not associated with daytime cortisol or DHEA secretion in the same subjects 41 . As previously mentioned, existing research presents contradictory findings on the associations between the DCS model dimensions and daytime cortisol secretion 23 24 25 26 27 28 29 30 31 32 33 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A DHEA szulfatálódásának, azaz a DHEAS termelődésének kizárólagos helye a szervezetben ez a réteg. A DHEA anti-GC hatása miatt számos tanulmány szerint a kortizol/DHEA arányt célszerűbb vizsgálni pusztán a GC-szintnél [6].…”
Section: A Szintézis Helyeunclassified